2015
DOI: 10.1111/dgd.12231
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of growth rate and developmental timing by Xenopus thyroid hormone receptor α

Abstract: Thyroid hormone (TH) is critical for vertebrate postembryonic development, a period around birth in mammals when plasma TH levels are high. Interestingly, TH receptors (TRs), especially TRa, are expressed prior to the synthesis and secretion of zygotic TH, suggesting the existence of unliganded TR during development. However, the role of unliganded TR during mammalian development has been difficult to study, in part due to the relatively weak phenotype of TR knockout mice. Amphibian metamorphosis resembles pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 96 publications
1
44
0
Order By: Relevance
“…Hormones and other small molecules act through nuclear receptors to initiate transcriptional cascades that often continue for extended periods of time. For example, thyroid hormone triggers metamorphosis in frogs and other chordates, a process that can take weeks for completion (60). Our work raises the possibility that nuclear receptors play an extensive and direct role in regulating activity of downstream response genes.…”
Section: Discussionmentioning
confidence: 99%
“…Hormones and other small molecules act through nuclear receptors to initiate transcriptional cascades that often continue for extended periods of time. For example, thyroid hormone triggers metamorphosis in frogs and other chordates, a process that can take weeks for completion (60). Our work raises the possibility that nuclear receptors play an extensive and direct role in regulating activity of downstream response genes.…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian metamorphic development is controlled by the thyroid hormone (reviewed in [35]), although little is known about hormonal control of the immune system transition besides MHC class I and II genes (reviewed in [36]). The possibility that carbaryl can affect leukocyte development is also consistent with the observed effect of carbaryl at a higher (10 μg/L or 10 ppb) dose, which considerably shortens the time to metamorphic completion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, limited studies on the intestine, an internal organ, have revealed relative minor effects of TRα or TRβ knockout during natural metamorphosis, mainly a delay in intestinal remodeling relative to the external morphological changes in the knockout tadpoles [56][57][58][59]. This seems to contrast with the strong upregulation of TRβ during intestinal metamorphosis in both Xenopus laevis and Xenopus tropicalis [36,54,55], two related anuran species that undergo very similar intestinal remodeling [38,47]. It is possible that the relatively minor effects observed for the TR knockouts during natural intestinal metamorphosis is in part due to comparing wild type and knockout animals of different ages (in order to match the stage) and/or due to distinct, developmental stage-dependent effects of the TR knockouts on the intestine and external organs that are used to determine the stages of the animals.…”
Section: Resultsmentioning
confidence: 99%
“…We have been studying amphibian metamorphosis as a model system for understanding the regulation of postembryonic vertebrate adult organ development by T3. During metamorphosis in anurans such as the pseudo-tetraploid Xenopus laevis and its highly related diploid species Xenopus tropicalis, T3 induces dramatic tissue modifications in essentially all tissues/organs [3,4,[32][33][34][35][36]. Of particular interest among them is intestinal remodeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation